Optimization of the bio-mechanical properties of Ti-8Si-2Mn alloy by 1393B3 bioactive glass reinforcement - Saxena V.; Kumar V.; Rai A.; Yadav R.; Gupta U.; Singh V.K.; Manna P.P. (My University, 2025)
The low cost Ti-8Si-2Mn alloy matrix has been synthesized by powder metallurgical route. The alloy is reinforced with 1393 B3 bioactive glass to optimize the mechanical and biological properties. The reinforced weight percentage of glass is 0% (S1), 5% (S2), 10% (S3) and 20% (S4). The physical, mechanical, biological and corrosion properties of these composites were investigated. The cell culture suggests that composite S1 and S3 support the growth of the tumor cells when used at lower concentration. The hardness of samples decreases with the increasing percentage of reinforced glass; however, the respective hardness is still superior to the cortical bone. The composite S3 shows better compressive strength (339 MPa), low Young's modulus (76 GPa), optimum density (2.71 gm cm-3) and hardness (381 Hv) as compared to pre-existing Ti implants. So it can be proposed as a new novel load bearing bio implant which will potentially reduce the stress shielding effect, toxicity and will improve the Osseo conductivity. © 2019 IOP Publishing Ltd.